The Use of social media In the Processes of Image-Building, Promotion and Military Recruitment: Case Study of The Territorial Defence Forces in Poland - Paulina POLKO; Michał SZYSZKA (Communications of International Proceedings, 2021)
Although somewhat unwillingly, practically all armies in the world use social media to (1) promote military service and recruitment, (2) establish the reputation and positive image of the organisation, and (3) maintain their relationship with already recruited, former or prospective soldiers. This article constitutes a qualitative and quantitative analysis of the use of social media by the Territorial Defence Forces in Poland in 2017–2019, i.e. for the purpose of creating a positive image of the newly-founded formation and maintaining relationships with their supporters and prospective recruits. The research conducted demonstrates (1) the consistency, attractiveness and coherence of communications which meet the criteria of communication via social media platforms, (2) the effectiveness of the implemented communication strategy resulting in an increase of the number of users and their activity and (3) the development of good practices adopted by other branches of the Armed Forces of the Republic of Poland.
Keywords: social media; media relations; Territorial Defence Forces; recruitment; army; Polish Armed Forces; communication of public institutions in the media